Efforts to Overcome Obstacles in The Process of Issuing Sailing Approval Letters at The Banjarmasin Class I Port Authority and Municipal Office - Nandhiva Syafira Zahra; Nurhayati; Meryanti (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Based on ‘Law of the Republic of Indonesia Number 17 of 2008 concerning Shipping, Ship Airworthiness is the state of a ship that meets the requirements of ship safety, prevention of water pollution from ships, manning, loading lines, loading, crew welfare and passenger health, ship legal status, safety management and prevention of pollution from ships, and ship safety management to sail in certain waters. The Sailing Approval Letter is specifically regulated in the Law of the Republic of Indonesia Number 17 of 2008 concerning Shipping’. One of the problems in ship accidents in shipping is the problem of a person's ability and expertise in carrying out their duties in providing ship seaworthiness letters, sailing permits, shipping safety and security, as well as all sea transportation shipping activities in Indonesian waters. The research method used is descriptive qualitative research, using direct observation to the object of research, namely by carrying out land practice for 6 months at the Banjarmasin Class 1 Port Authority and Municipal Office. The results of the study show that obstacles in the process of issuing sailing approval letters can be overcome by: 1) Implementing an effective and efficient bureaucracy, it can overcome the complaints of some service users so that the process of issuing a Sailing Approval letter does not take a long time, 2) Adding staff or implementing personnel on duty, and providing knowledge and skills about the knowledge of using the Inapornet system and overcoming Inapornet system disruptions, 3) Communication determines the success of achieving the objectives of carrying out work. Knowledge of what will be done can run if communication goes well, so that every decision and implementation rule must be communicated to the right staff or executor.